FAKTOR RISIKO NYERI PINGGANG BAWAH PADA PASIEN DEWASA MUDA DI POLIKLINIK SARAF RSUD DR ZAINOEL ABIDIN BANDA ACEH - Dessy Rakhmawati Emril, Asti Yuliadha (Neurona Majalah Kedokteran Neuro Sains, 2012)
INTRODUCTION LOW BACK PAIN LBP IS A COMMON HEALTH PROBLEM IN YOUNG ADULTS THAT MAY LEAD TO RECURRENT CHRONIC AND ACTIVITIES LIMITATION